An Islamic Approach to Educate Children on Financial Literacy - Tazkiyyah, Naila M; Hafidhuddin, Didin; Ibdalsyah, Ibdalsyah; Tanjung, Hendri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to explore the Islamic perspective on financial literacy education for children and to analyze whether the Qur'an and Hadith provide guidance on managing wealth, assets, and financial decision-making. The research employs a library research methodology, gathering data and documents from primary and secondary sources. Content analysis was used as the data analysis method to refine and expand upon existing theories. The findings reveal that, based on the interpretation of several Qur'anic verses, Hadiths (including insights into the wealth and economic practices of the Prophet Muhammad), and Islamic literature, the Islamic perspective recognizes financial literacy education for children as an essential component. However, its practical application must be tailored to align with the developmental stages of children.